Prototype Penjemur Pelepah Pinang berbasis Mikrokontroler dengan Sistem Kontrol Suhu PID - Yusuf, Roy Efendy; Misbah, Misbah; Surya, Yoedo Ageng (Universitas Mulawarman, 2025)
Pudak is a typical food from the province of East Java , Gresik district in the form of a traditional cake that has a sweet taste and very suitable for souvenirs because this food does not spoil easily and can last a long time. For the process so that it can be used as packaging for pudak, first of all the areca nut fronds are dried in the sun and depend on sunlight conditions for the drying process. A poor drying process results in poor quality of areca fronds. Apart from being susceptible to fungus, a less than optimal drying process can make pudak rots quickly. To overcome the problem of drying, this research was made, in order to increase the efficiency and productivity of areca nut farmers. The working process of this prototype uses 3 input sensors (DS18B20 sensor, LDR sensor, rain sensor) and is accompanied by a heater with a PID control system to stabilize the temperature during the drying process. The results indicate that the design system for this areca nut frond dryer is able to provide an effective solution in accelerating the drying process. This tool is proven to be able to dry areca nut fronds optimally in a relatively short time, which is around 20 hours. The system is equipped with a PID-based temperature control method using the Ziegler–Nichols tuning approach, which produces control parameters with values of Kp = 12.9, Ki = 1.22, and Kd = 0.3. These parameters produce a stable system response graph. The application of PID control contributes significantly to the quality of the areca nut fronds produced because the drying temperature can be maintained at a set point of 40°C consistently. The results of monitoring the drying process show that areca nut fronds weighing between 250 and 500 grams can be dried perfectly in a duration of 20 hours.